Knowledge on hand hygiene compliance among health care workers at surgical wards in Hospital Universiti Sains Malaysia - Aminudden, Syaidatull Asmara (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Practices hand hygiene, through methods washing the hands with water and soap or using alcohol-based hand rub, is a effective way to prevent infections. The healthcare worker, who is involved in patient care directly or indirectly, not practice properly on hand hygiene compliance because of their the knowledge were not satisfation. Thus, this study aims to assess the level knowledge and a barriers on hand hygiene compliance among health care workers in the surgical ward of Hospital Universiti Sains Malaysia. Total of 140 healthcare workers from wards 2 Intan and 3 Utara by category including physicians, specialist doctor, medical and surgical doctors, nurses, physiotherapists, dietitian and health care assistants were involved in this study. A cross-sectional study design was employed. Data was collected through a set of questionnaires adapted from Saharman et al. (2019) and analysed using SPSS version 26. Pearson Chi-Square Test was used to determine the association between socio-demographic characteristics with the knowledge level on hand hygiene compliance. The majority of the respondents in this study had good knowledge level on hand hygiene compliance (n=120, 86.0%). Among the five factors (age, gender, race, profession and work experience) , it also showed that there was no significant association with knowledge level as p-value > 0.05. These findings revealed that there was a need to increase healthcare workers awareness and improve their knowledge level and barriers on hand hygiene compliance as a preventive measure for further in preventing of healthcare associated infection (HCAIs).